LEMBAGA PENDIDIKAN SEBAGAI SUATU SISTEM SOSIAL (Studi Tentang Peran Lembaga Pendidikan di Indonesia Dalam Perspektif Undang-Undang Nomor 20 Tahun 2003 Tentang Sistem Pendidikan Nasional) - Mu'in Abdullah (Institut Islam Mamba'ul 'Ulum Surakarta, 2022)
Education and society cannot be separated. Education takes place in society while the existence and the quality of society’s life were determined by the level of education experienced. As a social institution, education grows and develops in society without knowing the level of culture, whether in traditional or modern society. Educational institutions are born as social institutions, start from kindergarteen, elementary, junior high, high school, and higher education. There are three kinds of educational institutions. That are formal, informal, and non-formal education. These three institutions are interdependent in realizing a better change of society from all sides. Educational institutions as a social system has an important role in understanding each individual because education expected can change the thinking patterns of people who have a complex character. The changes are expected to be better condition. Changes that exist in society will be very different due to the different levels of education and economic levels that exist within the community itself. Changes in the level of education will continue to occur in society as long as the community wishes to change them. When the community wants to change its social status, it is necessary education as a means to make it happen.